Nuclei‐specific deposits of iron and calcium in the rat thalamus after status epilepticus revealed with quantitative susceptibility mapping (QSM). Issue 2 (5th June 2017) - Aggarwal, Manisha; Li, Xu; Gröhn, Olli; Sierra, Alejandra
Abstract : Purpose: To investigate pathological changes in the rat brain after pilocarpine‐induced status epilepticus using quantitative susceptibility mapping (QSM). Materials and Methods: 3D multiecho gradient‐echo (GRE) data were acquired from ex vivo brains of pilocarpine‐injected and age‐matched control rats at 11.7T. Maps of R2* and quantitative susceptibility were calculated from the acquired 3D GRE magnitude and phase data, respectively. QSM and R2* maps were compared with Perls' (iron) and Alizarin‐red‐S (calcium) stainings in the same brains to investigate the pathophysiological basis of susceptibility contrast. Results: Bilaterally symmetric lesions were detected in reproducible thalamic regions of pilocarpine‐treated rats, characterized by hyperintensity in R2* maps. In comparison, quantitative susceptibility maps demonstrated heterogeneous contrast within the lesions, with distinct hyperintense (paramagnetic) and hypointense (diamagnetic) areas. Comparison with histological assessment revealed localized deposits of iron‐ and calcium‐positive granules in thalamic nuclei corresponding to paramagnetic and diamagnetic areas delineated in the susceptibility maps, respectively. Pronounced differences were observed in the lesions between background‐corrected phase images and reconstructed susceptibility maps, indicating unreliable differentiation of iron and calcium deposits in phase maps. Multiple linear regression showed a significant association between susceptibility values and measured optical densities (ODs) of iron and calcium in the lesions (R 2  = 0.42, P < 0.001), with a positive dependence on OD of iron and negative dependence on OD of calcium. Conclusion: QSM can detect and differentiate pathological iron and calcium deposits with high sensitivity and improved spatial accuracy compared to R2* or GRE phase images, rendering it a promising technique for diagnosing thalamic lesions after status epilepticus. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:554–564.